A Determining Method of the Project Quality Guarantee Deposit under the Condition of Asymmetric Information with the Contractor's Credit Level into Consideration. (30th May 2022) - Nie, Xiangtian; Zheng, Ye; Wang, Yuhao; Yang, Qi; Wang, Bo
Abstract : On the basis of analyzing the relationship between a contractor's credit, project quality assurance, owner's monitoring level, and the quality guarantee deposit, the quality expected benefit model of the owner and the contractor was constructed under the conditions of symmetric information and asymmetric information, in which the owner assumed the primary responsibility for the project quality, the project characteristics were incorporated, the credit level was taken as the contractor's decision variable, and the project quality monitoring level and detention of the quality guarantee deposit were taken as the owner's decision variables. In light of the maximum value principle, an optimal solution to the owner's quality monitoring decision and the quality deposit detention strategy was derived; through the simulation calculation, the decision-making results under different information conditions were analyzed.